FUNGSI ADVOKASI TERHADAP RESILIENSI DAN PENERIMAAN DIRI BAGI ANAK KORBAN PERCERAIAN - Kushendar Kushendar; Aprezo Pardodi Maba; M Sayyidul Abrori; Ervina Mukharomah; Hernisawati Hernisawati; Andika Ari Saputra (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2022)
The number of divorce cases that occur in a family leaves sadness, anger to sadness, many agree that the result of divorce is none other than children. The advocacy function is part of the form of guidance and counseling services, namely helping students in an effort to regain their rights that are not considered and or get wrong treatment in accordance with their rights and obligations. The purpose of this study was to determine the psychological condition seen from the aspect of resilience and self-acceptance with the efforts made by the counselor, namely the implementation of the advocacy function for children who are victims of parental divorce. The research method in this article is a case study with a qualitative descriptive approach. The findings were found to affect the mindset and psychological condition of the victim causing students to experience trauma and fear so that it had an impact on the psychology involved in the learning process which decreased and lacked enthusiasm or motivation even though X could be said to be tough. students, but it was known during the counseling that X felt sad, afraid and traumatized which had an impact on decreasing resilience and self-acceptance because he felt that these problems robbed the family of dignity.